AIRPORT AS A FACTOR SHAPING THE SOCIO-ECONOMIC SITUATION IN THE MUNICIPALITY IN A CHANGING REALITY - Marzena PIOTROWSKA-TRYBULL; Jarosław KOZUBA; Stanisław SIRKO (Scientific Journal of Silesian University of Technology. Series Transport)
Airports, as a component of air transport, combine air transport with other modes of transport to strengthen the transportation accessibility of a place in space, attract investors, and stimulate the development of the area. Taking into account that these issues are less exposed in relation to their immediate surroundings, research was undertaken to determine how representatives of the authorities and residents of communes (taking into account the nature of the communes and the size and location of the airport) perceive airports, located within their communes, in the context of their impact on the socio-economic situation in the communes. This was achieved by analysing the communes' strategic documents and data on the operation of communes and airports from 2016 to 2021. These data were obtained from the Civil Aviation Authority, the Central Statistical Office, the International Air Transport Association, and the International Airports Council. In an effort to better understand the relationship between the airport and the commune in which it is located, poll research was carried out using survey and interview techniques. The research focused on 10 airports spread across Poland. A total of 1,200 surveys were conducted among residents of communes, and 10 interviews were conducted with representatives of local governments and the port. To analyse the collected data and present the results, Statistica v.13.3 and R/RStudio software were used.